THE KNOWLEDGE AND THE FARMERS TO SUCCESSFUL IN BLM PUAP PROGRAME GAPOKTAN TRI LESTARI THEIR TRI TUNGGAL JAYA AGUNG BANJAR IN TULANG BAWANG DISTRICT (Sylva : Jurnal Penelitian Ilmu-Ilmu Kehutanan, 2022)
The research on the relationship between knowledge and attitudes of farmers towards the success of the BLM PUAP programe in Gapoktan Tri Lestari Tri Tunggal Jaya village District of Banjar Agung Tulang Bawang district aims to describe the knowledge and attitudes of farmers towards BLM PUAP programe success in Gapoktan District of Banjar Agung Tri Lestari Tulang Bawang district . The method used is a survey to farmers , farmer groups and board administrators farmer groups of 30 people to conduct interviews using questionnaires . 30 Sampling Random Sampling method Proporsonal . The results showed that the behavior of farmers viewed the success of the BLM PUAP programe components terahadap knowledge obtained an average score of 9.70 ( high criterion ) . This means that the knowledge of farmers on the success of the BLM PUAP programe has been very good means have known about the BLM PUAP programe , BLM PUAP programe objectives , indicators of program success PUAP BLM and the Finance Micro Agribusiness Institute . As for the attitude of farmers towards the success of the BLM PUAP programe obtained an average score of 9.37 ( high criterion ) means the farmer has agreed to fill out a registration form before becoming members , agree with the principal savings , mandatory savings members , agree with the distributions of Enterprises ( SHU ) at the end of the year and agreed to pay the loan each month